2010
DOI: 10.1007/s11859-010-0318-2
|View full text |Cite
|
Sign up to set email alerts
|

A biometric-based user authentication for wireless sensor networks

Abstract: This paper proposes a biometric-based user authentication protocol for wireless sensor networks (WSN) when a user wants to access data from sensor nodes, since WSN are often deployed in an unattended environment. The protocol employs biometric keys and resists the threats of stolen verifier, of which many are logged-in users with the same login identity, guessing, replay, and impersonation. The protocol uses only Hash function and saves the computational cost, the communication cost, and the energy cost. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 14 publications
(13 reference statements)
0
47
0
Order By: Relevance
“…Chen and Shih indicated that Das's scheme did not provide mutual authentication between the gateway and the sensor, and Chen and Shih proposed a robust mutual authentication scheme for WSNs and claimed that their scheme provides greater security than Das's scheme [10]. In 2010, Yuan et al [11] proposed a biometric-based user 2 International Journal of Distributed Sensor Networks authentication scheme, but it was found to have various security problems. Yoon and Yoo pointed out that Yuan et al 's scheme has vulnerability to insider, user impersonation, gateway node impersonation, and sensor node impersonation attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Shih indicated that Das's scheme did not provide mutual authentication between the gateway and the sensor, and Chen and Shih proposed a robust mutual authentication scheme for WSNs and claimed that their scheme provides greater security than Das's scheme [10]. In 2010, Yuan et al [11] proposed a biometric-based user 2 International Journal of Distributed Sensor Networks authentication scheme, but it was found to have various security problems. Yoon and Yoo pointed out that Yuan et al 's scheme has vulnerability to insider, user impersonation, gateway node impersonation, and sensor node impersonation attacks.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Yuan et al [13] provided a bio-metric based scheme but it is unprotected from node capture and denial of service attack. In 2012, Yoo et al [14] designed a scheme that provides secure session key and mutual authentication.…”
Section: Related Workmentioning
confidence: 99%
“…In 2013, Althobati et al [11] proposed an efficient remote user authentication protocol using biometric information [12][13][14][15]. The new technology of biometrics is becoming a popular method for engineers to design a more secure user authentication scheme.…”
Section: )mentioning
confidence: 99%